A novel semi-analytical approach for predicting the sound absorptions of a new underwater composite coating with transversely arranged SWCNTs. (15th October 2021) - Zhang, Zhifu; Li, Zhuang; Li, Tianyun; Huang, Qibai
Highlights: Innovative design of a new composite coating with transversely arranged SWCNTs. A novel semi-analytical approach with multi-scale features is proposed. A global TMM for vibroacoustic properties of orthotropic materials is developed. The new coating breaks the general lower limit of 500 Hz@0.5 to 193.1 Hz@0.5. Abstract: This paper presents a new underwater composite coating with transversely arranged single-walled carbon nanotubes (SWCNTs) to broaden the lower frequency limit of sound-absorbing and improve the broadband absorption bandwidth. Meanwhile, a novel semi-analytical approach integrating molecular dynamics simulation methodology and global generalized transfer matrix method (6 × 6) is proposed to predict the corresponding sound absorption characteristics. Then, the correctness and effectiveness of the present theoretical model are validated by means of an acoustic-structure fully coupled finite element simulation and theoretical predictions in turn. At last, influence laws of ten critical parameters on sound absorption coefficients are explored to reveal the multiple energy-dissipation mechanisms. The results show that the 0.5 absorption bandwidth of this coating is [0.1931, 50] kHz, which breaks the lower limit 0.5 kHz of the conventional low-frequency band and has a high-performance broadband absorption potential.